Molecular Docking Study of Pongamia pinnata Phytochemicals as Phosphodiesterase-4 Inhibitors for Atopic Dermatitis - Adinda Salsabila; Riska Arini; Tantri Liris Nareswari; Naura Nurnahari (MEDFARM: Jurnal Farmasi dan Kesehatan, 2026)
Atopic dermatitis is a chronic inflammatory skin disease characterized by recurrent itching, eczematous lesions, and associated with significant impairment in quality of life. Current therapies for AD, including corticosteroids and calcineurin inhibitors, are often associated with adverse effects, highlighting the need for safer alternatives. Pongamia pinnata is widely used in traditional medicine and has demonstrated anti-inflammatory and antioxidant properties. Therefore, this study aimed to explore the potential of P. pinnata phytochemicals as phosphodiesterase-4 inhibitors for atopic dermatitis through molecular docking analysis. Molecular docking analysis was conducted against phosphodiesterase-4 to evaluate their binding affinities and key amino acid residues compared to the native ligand and roflumilast as the reference drug. Subsequently, Lipinski’s Rule of Five was applied to assess the oral drug-likeness properties of the selected compounds. Karanjachromene exhibited the highest binding affinity toward PDE4 (ΔG = −8.17 kcal/mol), exceeding both the reference drug roflumilast (ΔG = −6.47 kcal/mol) and the native ligand (ΔG = −7.81 kcal/mol). Interaction analysis demonstrated that karanjachromene shared several key amino acid residues with the native ligand, indicating similar binding interactions with phosphodiesterase-4. In addition, karanjachromene fulfilled Lipinski’s Rule of Five and favorable ADMET properties, suggesting oral administration potential. However, further in vitro and in vivo evaluations are required to validate its pharmacokinetics, bioavailability, and pharmacological activity against phosphodiesterase-4.